Analisis Kinerja Keuangan PT. Ultrajaya Milk Industry and Trading Company Tbk Berdasarkan Rasio Likuiditas, Solvabilitas, dan Profitabilitas Tahun 2020-2021 - Hani Sutiyani (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to analyze the financial performance of PT. Ultrajaya Milk Industry and Trading Company Tbk in 2020–2021 based on liquidity, solvency, and profitability ratios. The study employs a descriptive approach to systematically illustrate the company's financial statements. The analytical findings reveal that liquidity ratios (Current Ratio and Quick Ratio) increased in 2021, reflecting the company's improved capacity to meet short-term obligations. Solvency ratios (Debt to Asset Ratio and Debt to Equity Ratio) showed significant improvement, indicating a progressively healthier capital structure. However, profitability ratios (Net Profit Margin, Return on Assets, and Return on Equity) experienced a slight decline due to increased operating expenses. This study presents practical applications for management in managing liquidity, debt, and cost efficiency.